Development of a software for intraoperatory nursing assistance. - dos Reis Machado, Gilberto; Martinez Évora, Yolanda Dora; Leite Rangel, Alexandre; Pereira Silveira, Renata Cristina de Campos; da Silva, Beatriz Regina (Revista Brasileira de Enfermagem)
Objective: to develop a software that allows the nurse of the surgical center to plan intraoperative nursing care through electronic access to the work routines of his/her team. Method: the methodological course was carried out according to systems development theory, which guides five basic activities: communication, planning, modeling, developing and delivery of the product. Results: the activities and functions of the software were arranged in five modules, containing information regarding the inputs and the step-by-step involving the assembly, circulation and disassembly of the operating room to perform the various anesthetic and surgical procedures. Final considerations: The developed software will allow the surgical center's nursing team to access its intraoperative routines in a fast and systematic way, since this allowed to concentrate all the routines of assembly, circulation and disassembly of operating room in a safe space and accessible